Transformasi Pendidikan Agama di Indonesia Pasca Kemerdekaan (1945-2025) - Muqofy, Ahmad (JoEMS (Journal of Education and Management Studies), 2024)
The transformation of Islamic education in Indonesia has undergone significant changes since 1945, influenced by social, political, and cultural dynamics. This study aims to understand this transformation process using a qualitative approach based on literature review. The findings reveal that Islamic education plays a central role in shaping Islamic identity and reinforcing Islamic values within society. The synergy between formal and informal education, particularly parental involvement in religious education at home, is crucial for the successful formation of Islamic character. Additionally, a multicultural approach in Islamic education has been shown to enhance cross-cultural understanding and strengthen social cohesion in a diverse society. Theoretically, this study enriches the understanding of the dynamics of Islamic education in shaping individual character and strengthening social integration. Methodologically, the literature review approach enables an in-depth exploration of various relevant policies and historical sources. Practically, the findings of this study serve as a reference for policymakers and education practitioners in developing a more adaptive, integrative, and responsive curriculum that addresses the challenges of globalization and moderniation. The uniqueness of this study lies in its broad historical scope and in-depth exploration of the relationship between Islamic education, Islamic identity, and social diversity. Thus, this study not only contributes academically to the field of Islamic education but also offers strategic perspectives for the development of more inclusive and sustainable education policies.